Analisis Bibliometrik Implementasi E-Learning Dalam Pendidikan Ekonomi - Akhmad Suyono; Andri Eko Prabowo; Nunuk Suryanti (Universitas Hamzanwadi, 2022)
Ongoing learning must be able to increase effectiveness in order to achieve educational goals. Technology and information that are currently developing have spread in various fields of human life, including education. The inclusion of technology and information in education has an impact on changes in both aspects of the education system, the material provided, including how the learning process is carried out and the obstacles that may be accepted by educators and students. This study aims to determine the implementation of e-learning in economics education to improve students' competence. This study uses bibliometric analysis to map e-learning in various previous research journals in relation to economic education using Vosviewer. The results of this study conclude that e-learning is a must in improving the competence of students, especially women who run home-based and small-scale business activities.